The Effectiveness of Modified Atkins Ketogenic Diet on Children with Intractable Epilepsy: A Pilot Study from Indonesia - Achmad Rafli; Setyo Handryastuti; Mulya Rahma Karyanti; Yoga Devaera; Cut Nurul Hafifah; Irawan Mangunatmadja; Muzal Kadim; Elisabeth Siti Herini; Lora Sri Nofi; Ariek Ratnawati; Suci Fitrianti (Journal of Nutrition and Metabolism)
Background. The ketogenic diet has recently been explored as a potential treatment approach for intractable epilepsy in children and has been applied in various parts of the world. The ketogenic diet is also effective for the treatment of mood disorders, especially for adolescent and young adults with epilepsy. The Modified Atkins Diet (MAD) is the less restrictive type of ketogenic diet with similar principles as the classic type. However, no study has been conducted to evaluate the use of MAD in children with severe epilepsy in Indonesia. This study aims to assess the effectiveness, tolerance, compliance, and the adverse effects of MAD in children with intractable epilepsy during a 6-month monitoring period. Methods. This is a pilot experimental study involving children aged 2–18 years old with intractable epilepsy at the Pediatric Neurology and the Pediatric Nutrition & Metabolic Diseases Clinics at the Dr. Cipto Mangunkusumo Hospital Jakarta between November 2021 and June 2022. Results. A total of 31 subjects met the inclusion criteria and received the MAD in the first month, followed by 13 (41.9%) subjects in the third month, and 9 (29%) subjects in the sixth month. The MAD reduced the seizure frequency by 50% (p=0.144), 62% (p=0.221), and 83.3% (p=0.028) in the first, third, and sixth months, respectively. The most frequent adverse effects are vomiting and diarrhea. Noncompliance was observed in 18 (58.1%) subjects. A sample of the MAD food menu guidebook was developed to make it easier for parents to adhere to the diet. Conclusions. The MAD reduces the mean seizure frequency in children with intractable epilepsy in the first, third, and sixth months, with a statistical significance in the sixth month. A further randomized, controlled, and multicenter clinical trial with a larger sample size and longer observation period is required. This trial is registered with Protocol ID 20-10-1323.